Cinnamon essential oil synergizes with sodium hypochlorite to suppress VBNC formation in Escherichia coli O157:H7 by modulating the temporal expression of arcA/relA-associated stress regulators - Haoqing Zhao; Zongwei Bai; Jingfeng Zhang; Yamei Chen; Huiting Huang; Xiaoxuan Wang; Jiawen Sun; Lei Shi; Xiaoli Xu; Lichao Zhao (Food Microbiology, 2027)

Establishment of a degenerate primer-based multiplex qPCR method for sensitive detection of Gas-Producing Bacillus spp. in soy sauce - Huiting Huang; Jingfeng Zhang; Haoqing Zhao; Zhongsong Chen; Qian zou; Yiling Jin; Xiaobo Zeng; Lichao Zhao (Food Microbiology, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Interfacial coordination and reinforcement mechanism in PBAT/Mica/MMT composites modified by Ca2+ and citric acid - Shunkai Yang; Jingfeng Huang; Xiangying Chen; Weiliang Tian (Applied Clay Science, 2026)

The rectal sac as a second liver for detoxification in the metamorphosing silkworm - Rongbing Chen; Jingfeng Yang; Shoulin Zhu; Erjun Ling; Qiuning Liu; Wuren Huang (Journal of Insect Physiology, 2026)

Constructing electronic-ionic bicontinuous networks for high-fidelity bioelectrical monitoring with 24-hour stable interfaces - Guangyuan Xu; Chuantian Ren; Weiguang Wang; Yufeng Wu; Yiqian Zhou; Ming Lei; Jingfeng Zhang; Kai Huang; Hui Wu (Chemical Engineering Journal, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Restraining grain growth and constructing defects in olivine-type silicate as high-performance cathode for rechargeable magnesium batteries - Jie Xu; Minjie Zhang; Rui Pu; Guangsheng Huang; Jingchao Zhang; Jianrong Zeng; Yanan Chen; Jingfeng Wang; Jili Yue; Fusheng Pan (Chemical Engineering Journal, 2026)

Spatiotemporal pattern of wheat harvest duration and its driving factors in the Huang-Huai-Hai plain of China - Renhai Zhong; Cong Chen; Guan Zhou; Xingguo Xiong; Qiyu Tian; Jingfeng Huang; Guangqiao Cao; Tao Lin (Computers and Electronics in Agriculture, 2026)

Anammox-based Multi-pathway biological nitrogen removal for high ammonia nitrogen wastewater treatment: Rapid startup and community response in pilot-scale application under starvation strategy - Guangchao Si; Li Zhang; Jingfeng Gao; Shujun Zhang; Zhibin Wang; Xiaowu Huang; Yongzhen Peng (Environmental Research, 2026)

High-sensitivity, multi-modal triboelectric sensor derived from Kevlar for self-powered Morse code transmission and human-machine interaction - Tao Huang; Zhaoqing Lu; Fengfeng Jia; Ruixue Pang; Huimei Zhao; Pengbo Yang; Chunting Li; Jingfeng Chen; Li Hua (Chemical Engineering Journal, 2026)

Preparation and digestive behavior of ferulic acid-bacterial cellulose/arabinoxylan complex with strong antioxidant activity - Xueqing Wang; Giorgia Purcaro; Yang Li; Jingjing Yang; Lang Jia; Jingfeng Li; Bei Fan; Yatao Huang; Fengzhong Wang; Lili Wang (Carbohydrate Polymers, 2026)

Forecasting of large-scale tea anthracnose in mountainous region of China though integration of multi-source habitat information with spatiotemporal phenological corrections - Yujuan Huang; Huiqin Ma; Cong Xu; Lin Yuan; Jingfeng Huang; Zijing Jin; Jingcheng Zhang (European Journal of Agronomy, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

Temporal Memory Mechanisms and Biome‐Specific Drivers of Ecosystem Carbon Flux: Insights From Explainable Deep Learning Modeling - Teng Ma; Wei He; Shuangxi Fang; Jingfeng Xiao; Ngoc Tu Nguyen; Hua Yang; Peipei Xu; Chengcheng Huang; Mengyao Zhao; Shuai Liu; Xinhui Lei; Ziyi Huang (Global Change Biology, 2026)
Ecosystem carbon dynamics are governed by complex temporal dependencies and environmental interactions, yet these processes remain poorly understood and quantified across diverse biomes. Here, we developed an explainable LSTM‐Attention framework that integrates LSTM networks, attention mechanisms, and gradient‐based attribution methods to reveal temporal dependencies in ecosystem carbon flux responses by analyzing eddy covariance flux measurements from 71 sites spanning eight North American biomes. Using this approach, we identified three distinct temporal memory patterns governing carbon flux responses. Grasslands exhibit short‐term memory dominance with exponentially increasing temporal contributions from distant to recent past. Deciduous broadleaf forests and wetlands show long‐term memory dominance, with deciduous broadleaf forests displaying the strongest historical dependence (attribution values declining from 0.30 at 6 months to 0.045 at 1 month). Croplands and evergreen needleleaf forests demonstrate U‐shaped dual memory patterns. Building on these temporal patterns, we identified biome‐specific environmental drivers operating within each memory framework: wetlands primarily controlled by soil moisture, evergreen needleleaf forests by radiation, and closed shrublands by vapor pressure deficit. Beyond individual drivers, we uncovered critical nonlinear interactions that diverged from linear correlations at most sites (55 of 71 with ρ

PSNet: A deep learning framework following hierarchical yield level concept for crop yield estimation - Renhai Zhong; Xingguo Xiong; Qiyu Tian; Jingfeng Huang; Linchao Zhu; Yi Yang; Tao Lin (Computers and Electronics in Agriculture, 2025)

Pre-occupation strategy towards high initial coulombic efficiency in Mn-based layer cathode for magnesium-based hybrid-ion batteries - Yipeng Liu; Baihua Qu; Junhao Zhang; Hongfei Zheng; Le Tong; Yue Hao; Dong Wang; Guangsheng Huang; Qian Li; Xiaoyuan Zhou; Dong-Liang Peng; Jingfeng Wang (Chemical Engineering Journal, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Net ecosystem exchange of CO2 and its driving mechanisms in an island forest nature reserve in southern China - Liangxu Wu; Shuya Xie; Xianglan Li; Pengpeng Tian; Zhe Xu; Yuting Huang; Jingfeng Xiao; Xintong Chen; Minghai Xu; Wei Chen; Houcai Cai (CATENA, 2025)

The impact of selenium fertilizer application on the yield, quality, and selenium accumulation characteristics of sweet potato - Huifeng Li; Yixuan Zhang; Yanqing Li; Yongmei Huang; Jingfeng Hua; Jie Yin; Dong Xiao; Tianyuan Chen (Acta Physiologiae Plantarum, 2025)

Removal and toxic intervention of polystyrene microplastics and nanoplastics by magnetic nano-Fe3O4 in spermatogonial GC-1 cells - Cheng Cheng; Yanfan Cui; Yujie Wang; Jingfeng Huang; Jiale Ma; Tao Luo; Wen Chen (Reproductive Toxicology, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

PSeqNet: A crop phenology monitoring model accounting for phenological associations - Qiyu Tian; Hao Jiang; Renhai Zhong; Xingguo Xiong; Xuhui Wang; Jingfeng Huang; Zhenhong Du; Tao Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Deciphering the interfacial electrochemistry of non-nucleophilic Mg(TFSI)2 as 4 V-class electrolyte for Mg batteries - Lu Zhang; Yuping Liu; Xiaolei Wang; Zhihong Cui; Chenlong Xiao; Changguo Chen; Jingfeng Wang; Guangsheng Huang; Dingfei Zhang; Fusheng Pan (Chemical Engineering Journal, 2025)

High-efficiency recovery of FePO4 from lithium extraction slag via SO2 reductive leaching and selective precipitation - Jie Li; Jiang Diao; Zhiqiu Lai; Hong-Yi Li; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Journal of Cleaner Production, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Novel polymer electrolytes for rechargeable magnesium batteries prepared based on deep eutectic solvents - Peng Yang; Xiaoping Liang; Yu Wang; Li Gao; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Chemical Engineering Journal, 2025)

Loss Function Optimization Method and Unsupervised Extraction Approach D-DBSCAN for Improving the Moving Target Perception of 3D Imaging Sonar - Jingfeng Yu; Aigen Huang; Zhongju Sun; Rui Huang; Gao Huang; Qianchuan Zhao (Journal of Marine Science and Engineering, 2025)
Imaging sonar is a crucial tool for underwater visual perception. Compared to 2D sonar images, 3D sonar images offer superior spatial positioning capabilities, although the data acquisition cost is higher and lacks open source references for data annotation, target detection, and semantic segmentation. This paper utilizes 3D imaging sonar to collect underwater data from three types of targets with 1534 effective frames, including a tire, mannequin, and table, in Liquan Lake, Shanxi Province, China. Based on these data, this study focuses on three innovative aspects as follows: rapid underwater data annotation, loss function optimization, and unsupervised moving target extraction in water. For rapid data annotation, a batch annotation method combining human expertise and multi-frame superposition is proposed. This method automatically generates single-frame target detection boxes based on multi-frame joint segmentation, offering advantages in speed, cost, and accuracy. For loss function optimization, a density-based loss function is introduced to address the issue of overfitting in dense regions due to the uneven distribution of point cloud data. By assigning different weights to data points in different density regions, the model pays more attention to accurate predictions in a sparse area, resulting in a 6.939 improvement in mIOU for semantic segmentation tasks, while lakebed mIOU achieved a high score of 99.28. For unsupervised moving target extraction, a multi-frame joint unsupervised moving target association extraction method called the Double DBSCAN, D-DBSCAN, is proposed. This method simulates human visual sensitivity to moving targets in water and uses a joint D-DBSCAN spatial clustering approach with single-frame and inter-frame superposition, achieving an improvement of 21.3 points in mAP. Finally, the paper summarizes the three proposed innovations and provides directions for further research.

Reduced Erosion Augments Soil Carbon Storage Under Cover Crops - Wenjuan Huang; Lifen Jiang; Jian Zhou; Hyung‐Sub Kim; Jingfeng Xiao; Yiqi Luo (Global Change Biology, 2025)
Cover crops, a promising strategy to increase soil organic carbon (SOC) storage in croplands and mitigate climate change, have typically been shown to benefit soil carbon (C) storage from increased plant C inputs. However, input‐driven C benefits may be augmented by the reduction of C outputs induced by cover crops, a process that has been tested by individual studies but has not yet been synthesized. Here we quantified the impact of cover crops on organic C loss via soil erosion (SOC erosion) and revealed the geographical variability at the global scale. We analyzed the field data from 152 paired control and cover crop treatments from 57 published studies worldwide using meta‐analysis and machine learning. The meta‐analysis results showed that cover crops widely reduced SOC erosion by an average of 68% on an annual basis, while they increased SOC stock by 14% (0–15 cm). The absolute SOC erosion reduction ranged from 0 to 18.0 Mg C −1 ha −1 year −1 and showed no correlation with the SOC stock change that varied from −8.07 to 22.6 Mg C −1 ha −1 year −1 at 0–15 cm depth, indicating the latter more likely related to plant C inputs. The magnitude of SOC erosion reduction was dominantly determined by topographic slope. The global map generated by machine learning showed the relative effectiveness of SOC erosion reduction mainly occurred in temperate regions, including central Europe, central‐east China, and Southern South America. Our results highlight that cover crop‐induced erosion reduction can augment SOC stock to provide additive C benefits, especially in sloping and temperate croplands, for mitigating climate change.

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Habitat quality evaluation and pattern simulation of coastal salt marsh wetlands - Yuting Huang; Guanghui Zheng; Xianglan Li; Jingfeng Xiao; Zhe Xu; Pengpeng Tian (Science of The Total Environment, 2024)

An automatic tracking method for fruit abscission of litchi using convolutional networks - Tong Huang; Jingfeng Guo; Long Yu; Houbin Chen; Zuanxian Su; Yueju Xue (Computers and Electronics in Agriculture, 2024)

Global convergence in terrestrial gross primary production response to atmospheric vapor pressure deficit - Chao Huang; Jingfeng Huang; Jingfeng Xiao; Xing Li; Hong S. He; Yu Liang; Fusheng Chen; Hanqin Tian (Science China Life Sciences, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Optimization of the electrode reaction kinetics of V2O5 via polyacrylonitrile intercalation for high-performance magnesium batteries - Rongrui Deng; Zhongting Wang; Shuangshuang Tan; Xueting Huang; Zhipeng Gao; Yongheng Fang; Chunfeng Chen; Ronghua Wang; Chaohe Xu; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Chemical Engineering Journal, 2024)

Mechanisms and clinical application of Xuebijing injection, a traditional Chinese herbal medicine–a systematic review - Mengchi Chen; Wenbo Shu; Jingfeng Zhang; Hongyuan Huang; Jianghua Liu (Advances in Traditional Medicine, 2024)

Spatial distribution characteristics and interaction effects of DOM and microbial communities in kelp cultivation areas - Huiling Huang; Shuaijun Zan; Kuishuang Shao; Hanjun Chen; Jingfeng Fan (Science of The Total Environment, 2024)

Daily DeepCropNet: A hierarchical deep learning approach with daily time series of vegetation indices and climatic variables for corn yield estimation - Xingguo Xiong; Renhai Zhong; Qiyu Tian; Jingfeng Huang; Linchao Zhu; Yi Yang; Tao Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Remote sensing image cloud detection using a shallow convolutional neural network - Dengfeng Chai; Jingfeng Huang; Minghui Wu; Xiaoping Yang; Ruisheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Cleaning and upgrading of low-rank coal using a novel rotary triboelectric separator with the polyvinyl chloride as friction medium - Bin Yang; Lingtao Zhu; Jingfeng He; Bin Liu; Shibo Huang; Hao Chen; Wenjie Tang (Fuel, 2024)

Integration of harvester trajectory and satellite imagery for large-scale winter wheat mapping using deep positive and unlabeled learning - Xingguo Xiong; Jie Yang; Renhai Zhong; Jinwei Dong; Jingfeng Huang; K.C. Ting; Yibin Ying; Tao Lin (Computers and Electronics in Agriculture, 2024)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Label-free proteomics analysis on the envelope of budded viruses of Bombyx mori nucleopolyhedrovirus harboring differential localized GP64 - Bifang Hao; Jingfeng Li; Congcong Sun; Jinshan Huang (Virus Genes, 2023)

Surface modification to enhance the decarbonization performance of coal-series kaolin by triboelectric separation - Jingfeng He; Xin Zhang; Qiang Bai; Shibo Huang; Hao Chen; Chengjing Guo; Lingtao Zhu; Bin Yang (Applied Clay Science, 2023)

16S Next-generation sequencing and quantitative PCR reveal the distribution of potential pathogens in the Liaohe Estuary - Huiling Huang; Shuaijun Zan; Hongxia Ming; Mengfei Li; Jianrong Xu; Yuyang Xie; Wenjing Wang; Jingfeng Fan (Frontiers in Marine Science, 2022)
The existence of potentially pathogenic bacteria seriously threatens aquatic animals and human health. Estuaries are closely related to human activities, and the detection of pathogens is important for aquaculture and public health. However, monitoring only indicator microorganisms and pathogens is not enough to accurately and comprehensively estimate water pollution. Here, the diversity of potentially pathogenic bacteria in water samples from the Liaohe estuary was profiled using 16S next-generation sequencing (16S NGS) and quantitative polymerase chain reaction (qPCR) analysis. The results showed that the dominant genera of environmental pathogens were Pseudomonas , Vibrio , Mycobacterium , Acinetobacter , Exiguobacterium , Sphingomonas , and Legionella , and the abundance of enteric pathogens was significantly less than the environmental pathogens, mainly, Citrobacter , Enterococcus , Escherichia-Shigella , Enterobacter , Bacteroides . The qPCR results showed that the 16S rRNA genes of Vibrio were the most abundant, with concentrations between 7.06 and 9.48 lg copies/L, followed by oaa gene, fliC gene, trh gene, and uidA gene, and the temperature and salinity were the main factors affecting its abundance. Variance partitioning analysis (VPA) analysis of spatial factors on the potential pathogen’s distribution (19.6% vs 5.3%) was greater than environmental factors. In addition, the co-occurrence analysis of potential pathogens in the estuary revealed significant co-occurrence among the opportunistic pathogens Testosteronemonas , Brevimonas vesicularis , and Pseudomonas putida . Our findings provide an essential reference for monitoring and occurrence of potentially pathogenic bacteria in estuaries.

A deep learning approach to conflating heterogeneous geospatial data for corn yield estimation: A case study of the US Corn Belt at the county level - Hao Jiang; Hao Hu; Renhai Zhong; Jinfan Xu; Jialu Xu; Jingfeng Huang; Shaowen Wang; Yibin Ying; Tao Lin (Global Change Biology, 2020)
Understanding large‐scale crop growth and its responses to climate change are critical for yield estimation and prediction, especially under the increased frequency of extreme climate and weather events. County‐level corn phenology varies spatially and interannually across the Corn Belt in the United States, where precipitation and heat stress presents a temporal pattern among growth phases (GPs) and vary interannually. In this study, we developed a long short‐term memory (LSTM) model that integrates heterogeneous crop phenology, meteorology, and remote sensing data to estimate county‐level corn yields. By conflating heterogeneous phenology‐based remote sensing and meteorological indices, the LSTM model accounted for 76% of yield variations across the Corn Belt, improved from 39% of yield variations explained by phenology‐based meteorological indices alone. The LSTM model outperformed least absolute shrinkage and selection operator (LASSO) regression and random forest (RF) approaches for end‐of‐the‐season yield estimation, as a result of its recurrent neural network structure that can incorporate cumulative and nonlinear relationships between corn yield and environmental factors. The results showed that the period from silking to dough was most critical for crop yield estimation. The LSTM model presented a robust yield estimation under extreme weather events in 2012, which reduced the root‐mean‐square error to 1.47 Mg/ha from 1.93 Mg/ha for LASSO and 2.43 Mg/ha for RF. The LSTM model has the capability to learn general patterns from high‐dimensional (spectral, spatial, and temporal) input features to achieve a robust county‐level crop yield estimation. This deep learning approach holds great promise for better understanding the global condition of crop growth based on publicly available remote sensing and meteorological data.

Mapping high temperature damaged area of paddy rice along the Yangtze River using Moderate Resolution Imaging Spectroradiometer data - Yujie Dou; Ran Huang; Lamin R. Mansaray; Jingfeng Huang (International Journal of Remote Sensing, 2020)

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Multiple hydrological models comparison and an improved Bayesian model averaging approach for ensemble prediction over semi-humid regions - Wenbo Huo; Zhijia Li; Jingfeng Wang; Cheng Yao; Ke Zhang; Yingchun Huang (Stochastic Environmental Research and Risk Assessment, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Revisiting the global surface energy budgets with maximum-entropy-production model of surface heat fluxes - Shih-Yu Huang; Yi Deng; Jingfeng Wang (Climate Dynamics, 2017)

Mapping deforestation and urban expansion in Freetown, Sierra Leone, from pre- to post-war economic recovery - Lamin R. Mansaray; Jingfeng Huang; Alimamy A. Kamara (Environmental Monitoring and Assessment, 2016)

Detection of vegetation abundance change in the alpine tree line using multitemporal Landsat Thematic Mapper imagery - Yaoliang Chen; Dengsheng Lu; Geping Luo; Jingfeng Huang (International Journal of Remote Sensing, 2015)

Impacts of land-cover types on an urban heat island in Hangzhou, China - Li Sheng; Dengsheng Lu; Jingfeng Huang (International Journal of Remote Sensing, 2015)

Trends in the daily and extreme temperatures in the Qiantang River basin, China - Fang Xia; Xingmei Liu; Jianming Xu; Zhonggen Wang; Jingfeng Huang; Philip C. Brookes (International Journal of Climatology, 2015)
Temporal and spatial changes in the annual and seasonal temperatures in a typical basin of the Qiantang River were analysed based on the time series databases of daily temperatures from 14 meteorological stations. Both the Mann–Kendall ( MK ) trend test and simple linear regression analyses were employed to detect trends in the mean and extreme temperatures. The temperature changes during the three periods of 1960–1990, 1960–2000 and 1960–2006 were investigated at each meteorological station and over the entire basin as an average. The spatial and temporal changes were characterized by significant warming throughout the region, with the minimum temperature (Tn) increasing the most, particularly after 1990. Various percentiles of extreme temperatures, as well as their corresponding frequencies, were chosen to explore the trends of extreme climate change in this region. Linear regression analyses showed a significant warming trend in cold events both on an annual and seasonal basis, especially in the winter. Conversely, the hot events were dominated by an insignificant warming trend ( p > 0.05). When comparing the time series before and after 1990, trend shifts were apparent in both the mean and extreme temperatures, particularly in the spring and winter. In addition to the large‐scale circulation, regional factors may have influenced the observed climate change in the studied region. Climate change has already influenced human society by, for example, increasing the frequency of haze in the study region. We conclude that the warming here is mainly attributed to changes in the minimum temperature.

The detection and measurement of interleukin-6 in venous and capillary blood samples, and in sweat collected at rest and during exercise - Steve H. Faulkner; Kate L. Spilsbury; James Harvey; Andrew Jackson; Jingfeng Huang; Mark Platt; Alfred Tok; Myra A. Nimmo (European Journal of Applied Physiology, 2014)

Estimating nitrogen concentration in rape from hyperspectral data at canopy level using support vector machines - Fumin Wang; Jingfeng Huang; Yuan Wang; Zhanyu Liu; Fayao Zhang (Precision Agriculture, 2013)

Functional study of immature dendritic cells co-transfected with IL-10 and TGF-beta 1 genes in vitro - Lihong Chen; Minglian Qiu; Wubing He; Aimin Huang; Jingfeng Liu (Molecular Biology Reports, 2012)

Estimating biophysical parameters of rice with remote sensing data using support vector machines - XiaoHua Yang; JingFeng Huang; YaoPing Wu; JianWen Wang; Pei Wang; XiaoMing Wang; Alfredo R. Huete (Science China Life Sciences, 2011)

Evaluating the performance of PC-ANN for the estimation of rice nitrogen concentration from canopy hyperspectral reflectance - Qiuxiang Yi; Jingfeng Huang; Fumin Wang; Xiuzhen Wang (International Journal of Remote Sensing, 2010)

Validation of artificial neural network techniques in the estimation of nitrogen concentration in rape using canopy hyperspectral reflectance data - Yuan Wang; Fumin Wang; Jingfeng Huang; Xiuzhen Wang; Zhanyu Liu (International Journal of Remote Sensing, 2009)

Sub‐pixel reflectance unmixing in estimating vegetation water content and dry biomass of corn and soybeans cropland using normalized difference water index (NDWI) from satellites - Jingfeng Huang; Daoyi Chen; M. H. Cosh (International Journal of Remote Sensing, 2009)

Forms and balance of nitrogen and phosphorus in cage culture waters in Guangdong Province, China - Yanmao Wen; Xiange Wei; Tingfei Shu; Jingfeng Zhou; Guanghui Yu; Feng Li; Yanyun Huang (Chinese Geographical Science, 2007)